(untitled) (Fiep Bulletin - online, 2014)
INTRODUCTION: The Cardiac Rehabilitation is an interdisciplinary program which aims at improving physical, mental and social conditions in cardiopathological patients. The hydrocinesiotherapy is a different and pleasant way to achieve those gains, since it provokes many physiological alterations. OBJECTIVE: Evaluating the short-term aquatic 3rd phase cardiac rehabilitation in post Acute Myocardium Failure (AMF) patients through hydrocinesiotherapy in warming pools. METHODOLOGY: A descriptive study of case with quantitative approach. The sample was constituted of 2 people, average age 63.5 years-old, on the 3rd phase post-AMF, REVICARDIO Project participants. The evaluation was consisted of anamnesis, physical exam, 6-minute walk test and aquatic abilities. The training was divided into 6 steps, all of them monitored through a POLAR FS1 heartbeat measure by checking people’s arterial pressure and breath frequency in the beginning and end of each session. The training protocol consisted of exercises of lengthening, warming-up, breath frequency, aerobics, diswarming and relaxing, twice a week, for 7 weeks, average 90-minute lasting. RESULTS: In the 6’ WT test, the anticipated traversed distance inceased 17.4% in A, and 21% in B. The final heartbeat test was 57.1% inferior to the initial one in A sessions, and 64.3% in B. CONCLUSION: The water exercise was pleasant, however it is necessary a long-term physical preparation with an intensive observation by the interdisciplinary staff. Then there is the necessity of more sample long-term studies.